Self-initiated physical activity is associated with high sensitivity C-reactive protein: A longitudinal study in 5,030 adults - Fernandes, Rômulo Araújo [UNESP]; Ritti-Dias, Raphael Mendes; Balagopal, P. Babu; Conceição, Raquel D.O.; Santos, Raul D.; Cucato, Gabriel Grizzo; Bittencourt, Márcio Sommer (Elsevier, 2018)
Background and aims: Structured regular exercise programs decrease high-sensitivity C-reactive protein (hsCRP), a marker of low-grade inflammation in adults. Longitudinal effects of self-initiated physical activity levels (PAL) on hsCRP are less clear. This study evaluated the association of longitudinal changes in hsCRP in relation to modifications in PAL, over time, in a large sample of adults. Methods: Participants included 5030 adults, 4045 (80%) males, undergoing routine health screening examinations. Elevated level of hsCRP was defined as ≥3 mg/L. Self-reported PAL, height, weight, blood pressure and blood samples were collected at baseline and after a median of 2.9 years (P25th 1.97 and P75th 4.37 yrs). Participants were stratified according to their PAL at baseline and follow-up as: i) persistently physically inactive; ii) became physically inactive; iii) became physically active; iv) persistently physically active (active both at baseline and follow-up). Results: Persistently physically active participants had lower odds of having higher hsCRP (OR = 0.35 [95% CI: 0.25 to 0.48]). The maintenance of high PAL was associated with lower hsCRP in both sexes (men: OR = 0.44 [0.30 to 0.65] and women: OR = 0.35 [0.16 to 0.76]). Participants with overweight/obesity (OR = 0.43 [95% CI: 0.29 to 0.63]) and smokers (OR = 0.123 [95% CI: 0.03 to 0.60]) who were persistently active had lower odds of having higher hsCRP compared to physically inactive peers. Conclusions: Self-initiated PAL was longitudinally associated with hsCRP in adults. The data suggest that the initiation or maintenance of PA attenuates the low-grade inflammatory state, independent of sex, body weight and smoking status.
Keywords: Body mass index; C reactive protein; Cardiovascular risk; Exercise; Inflammation